Cyber Public Relations pada Kampanye Sadar Wisata 5.0 Kementerian Pariwisata dan Ekonomi Kreatif - Syafina Nur Inayah; Syifa Astasia Utari (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2025)
The 5.0 tourism awareness campaign is a program implemented by the Ministry of Tourism and Creative Economy. The campaign can run optimally if supported by the right communication strategy, one of which is cyber public relations. Cyber public relations plays an important role in disseminating campaign messages by involving the community and providing a positive image. This research aims to find out cyber public relations in the campaign by using a descriptive qualitative approach and cyber public relations theory proposed by Philps & Young (2009). The research data was obtained through primary data, namely interviews and secondary data, literature studies, observation. The results showed that the 5.0 tourism awareness campaign managed by Kemenparekraf emphasized the importance of transparency, the use of the internet, and quality content in delivering information to the public. By utilizing digital media, this campaign succeeded in raising awareness, changing attitudes, and encouraging positive public behavior towards tourism. The management of cyber public relations plays an important role in reaching a wide audience, including in remote areas, and ensuring the long-term sustainability and success of this campaign in supporting the development of sustainable tourism in Indonesia.